Inovasi Takoyaki dengan Proporsi Tepung Terigu dan Tepung Ubi Jalar Putih (Ipomea Batatas Linneas) dengan Penambahan Krimer Bubuk - Fitrotul Laili Maulidiya; Ita Fatkhur Romadhoni; Niken Purwidiani; Ila Huda Puspita Dewi (Garina, 2024)
This research aims to develop takoyaki by substituting wheat flour using white sweet potato flour (Ipomea Batatas Linneas) and adding powdered creamer. White sweet potatoes were chosen for their high nutritional content and ability to improve texture and taste. Apart from that, processing white sweet potatoes into flour can extend the shelf life and increase the economic value of local agricultural products. The addition of powdered creamer can produce takoyaki with a softer texture and provides a creamy touch which increases the appeal of the final product. Organoleptic tests were carried out on 40 panelists to assess the criteria for shape, color (outside and inside), aroma, texture, taste and overall preference for whether it was well received by consumers. The research results showed that the proportion of 90% wheat flour and 10% white sweet potato flour produced the best quality takoyaki based on organoleptic test scores. Apart from that, takoyaki products with a proportion of wheat flour and white sweet potato flour with the addition of powdered creamer contain 12.85% protein, 4.03% fat, 41.05% carbohydrates which have a high fiber content compared to conventional takoyaki. The cost of raw materials for takoyaki with the proportion of wheat flour and white sweet potato flour (Ipomea Batatas Linneas) is Rp. 40,365. The selling price of Takoyaki with a proportion of wheat flour and white sweet potato flour (Ipomea Batatas Linneas) is 19,000/portion.